Meat quality of gilts fed different ractopamine concentrations in diet Qualidade da carne de fêmeas suínas alimentadas com diferentes concentrações de ractopamina na dieta - Watanabe P.H. (2012)
A study was conducted to evaluate the physical, chemical and sensorial quality and fat acids profile of meat from gilts fed diets containing increasing concentration of ractopamine. A total of 468 gilts with initial weight of 84.77±7.20kg were allotted into 36 pens and fed diets containing 0, 5, 10 or 15mg of ractopamine/kg. After an experimental period of 28 days, two animals from each pen were chosen and slaughtered after 15 hours of fasting. A sample of the Longissimus muscle was collected to evaluate the quality of the pork meat. There was no effect (P>0.05) of ractopamine inclusion in pH, water holding capacity, shear force, color and lipid oxidation. However, a quadratic trend was observed (P<0.05) for cooking loss by increasing concentration of ractopamine in diets. For sensorial analysis of the Longissimus muscle, no differences were noted (P>0.05). No effects were observed (P>0.05) for fat acids profile and saturated and unsaturated fat acids ratio. In conclusion, the increase of up to 15mg of ractopamine/kg concentration in the diet does not change the physical and sensorial characteristics and the fat acids profile of meat from gilts slaughtered at 110kg of body weight.